Cell Therapy Biomanufacturing: Integrating Biomaterial and Flow‐Based Membrane Technologies for Production of Engineered T‐Cells. Issue 6 (25th January 2023) - Bomb, Kartik; LeValley, Paige J.; Woodward, Ian R.; Cassel, Samantha E.; Sutherland, Bryan P.; Bhattacharjee, Arnab; Yun, Zaining; Steen, Jonathan; Kurdzo, Emily; McCoskey, Jacob; Burris, David; Levine, Kara; et al.
Abstract: Adoptive T‐cell therapies (ATCTs) are increasingly important for the treatment of cancer, where patient immune cells are engineered to target and eradicate diseased cells. The biomanufacturing of ATCTs involves a series of time‐intensive, lab‐scale steps, including isolation, activation, genetic modification, and expansion of a patient's T‐cells prior to achieving a final product. Innovative modular technologies are needed to produce cell therapies at improved scale and enhanced efficacy. In this work, well‐defined, bioinspired soft materials are integrated within flow‐based membrane devices for improving the activation and transduction of T‐cells. Hydrogel coated membranes (HCM) functionalized with cell‐activating antibodies are produced as a tunable biomaterial for the activation of primary human T‐cells. T‐cell activation utilizing HCMs lead to highly proliferative T‐cells that express a memory phenotype. Further, transduction efficiency is improved by several folds over static conditions by using a tangential flow filtration (TFF) flow‐cell, commonly used in the production of protein therapeutics, to transduce T‐cells under flow. The combination of HCMs and TFF technology leads to increased cell activation, proliferation, and transduction compared to current industrial biomanufacturing processes. The combined power of biomaterials with scalable flow‐through transduction techniques provides future opportunities for improving the biomanufacturing of ATCTs. Abstract : Well‐defined, bioinspired soft materials are integrated within scalable, flow‐based membrane devices for improving the activation and transduction of T‐cells, which are essential steps in the production of adoptive T‐cell therapies. These innovative technologies provide opportunities for improving the manufacturing of cell therapies.